Culturally Intelligent Leadership - Moua, Mai (Business Expert Press, 2010)
Ebook from IG Library ; Outlines the ideas of cultural intelligence and the steps that must be considered and then practiced to become a culturally intelligent leader. This book includes the understanding culture and its impact on organizations, the strategic value of cultural intelligence, and practicing cultural intelligence in everyday business life.